Iron Formations as the Source of the West African Magnetic Crustal Anomaly - Launay, Nicolas; Quesnel, Yoann; Rochette, Pierre; Demory, François (Frontiers in Earth Science, 2018)
The geological sources of major magnetic field anomalies are still poorly constrained, in terms of nature, geometry and vertical position. A common feature of several anomalies is their spatial correlation with cratonic shields and, for the largest anomalies, with Banded Iron Formations (BIF). This study first unveils the magnetic properties of some BIF samples from Mauritania, where the main part of the West African magnetic anomaly is observed. It shows how strong the magnetic susceptibility and natural remanent magnetization for such rocks are. High Koenigsberger ratios imply that the remanent magnetization should be taken into account to explain the anomaly. A numerical modeling of the crust beneath this anomaly is performed using these constraints and both gravity and magnetic field data. A forward approach is used, investigating the depth, thickness and magnetization intensity of all possible crustal lithologies. Our results show that BIF slices can be the only magnetized crustal sources needed to explain the anomaly, and that they could be buried several kilometers deep. The results of this study provide a new perspective to address the investigation of magnetic field anomaly sources in other cratonic regions with BIF outcrops.